Direct analysis by time‐of‐flight secondary ion mass spectrometry reveals action of bacterial laccase‐mediator systems on both hardwood and softwood samples. Issue 1 (13th March 2018) - Goacher, Robyn E.; Braham, Erick J.; Michienzi, Courtney L.; Flick, Robert M.; Yakunin, Alexander F.; Master, Emma R.
Abstract : The modification and degradation of lignin play a vital role in carbon cycling as well as production of biofuels and bioproducts. The possibility of using bacterial laccases for the oxidation of lignin offers a route to utilize existing industrial protein expression techniques. However, bacterial laccases are most frequently studied on small model compounds that do not capture the complexity of lignocellulosic materials. This work studied the action of laccases from Bacillus subtilis and Salmonella typhimurium (EC 1.10.3.2) on ground wood samples from yellow birch ( Betula alleghaniensis ) and red spruce ( Picea rubens ). The ability of bacterial laccases to modify wood can be facilitated by small molecule mediators. Herein, 2, 2'‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulphonic acid) (ABTS), gallic acid and sinapic acid mediators were tested. Direct analysis of the wood samples was achieved by time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS), a surface sensitive mass spectrometry technique that has characteristic peaks for H, G and S lignin. The action of the bacterial laccases on both wood samples was demonstrated and revealed a strong mediator influence. The ABTS mediator led to delignification, evident in an overall increase of polysaccharide peaks in the residual solid, along with equal loss of G and S‐lignin peaks. The gallic acid mediator demonstrated minimal laccase activity. Meanwhile, the sinapic acid mediator altered the S/G peak ratio consistent with mediator attaching to the wood solids. The current investigation demonstrates the action of bacterial laccase‐mediator systems directly on woody materials, and the potential of using ToF‐SIMS to uncover the fundamental and applied role of bacterial enzymes in lignocellulose conversion.